(untitled) (Journal of Hama University, 2023)
To determine the most important problems faced by the fourth year students (class teacher) in the practical Education course from their point of view, the search has been applied on a sample of (48) male and female fourth year students (class teacher) at the Faculty of Education at the university of Hama at the child rearing department, and study the effect of gender, and school location where practical Education is applied. The search adopted the descriptive analytical method, for this purpose a questionnaire consisting of five axes about the most important problems faced by the fourth year students (class teacher) in the practical Education course with problems specific to the nature of the practical Education program ,practical Education supervisor, cooperating school, cooperating teacher, student teacher character. Results showed order of problems in descending order cooperating school problems in the first place ,practical Education supervisor problems in the last place. There were statistically significant differences according to the gender for males . There were no statistically significant differences according to the school location . In light of the results, the research presented some suggestions including holding regular meetings with cooperating school principals and teachers, and discuss the most important problems faced by the students.